2009
DOI: 10.1007/s10439-009-9749-3
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Dynamic Deformation of the Mitral Valve Annulus

Abstract: Though mitral valve (MV) repair surgical procedures have increased in the United States [Gammie, J. S., et al. Ann. Thorac. Surg. 87(5):1431-1437, 2009 Nowicki, E. R., et al. Am. Heart J. 145(6):1058-1062], studies suggest that altering MV stress states may have an effect on tissue homeostasis, which could impact the long-term outcome [Accola, K. D., et al. Ann. Thorac. Surg. 79(4):1276-1283 Fasol, R., et al. Ann. Thorac. Surg. 77(6):1985-1988, 2004; Flameng, W., P. Herijgers, and K. Bogaerts. Circulation 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…This work agrees with a previous in vivo study showing that the lateral annulus contracts more than the septal region of the annulus, and we have now correlated this observed behavior with the extracellular matrix structure and cell behavior in these regions [19]. It should be noted that contraction in the commissures was reported as being limited in the previous study, whereas in this study commissural contraction was not significantly different from contraction of the lateral annulus.…”
Section: Discussionsupporting
confidence: 92%
“…This work agrees with a previous in vivo study showing that the lateral annulus contracts more than the septal region of the annulus, and we have now correlated this observed behavior with the extracellular matrix structure and cell behavior in these regions [19]. It should be noted that contraction in the commissures was reported as being limited in the previous study, whereas in this study commissural contraction was not significantly different from contraction of the lateral annulus.…”
Section: Discussionsupporting
confidence: 92%
“…Eckert et al 13 previously reported strain and curvature in the ovine mitral annulus. Their peak strains in the septal and lateral regions are in excellent agreement with our findings both in systole and in diastole.…”
Section: Model Validationmentioning
confidence: 97%
“…Linear interpolation has been widely used among clinical researchers to characterize the mitral annulus in humans and in animal models. 18,20,21,48 More sophisticated approaches use one-dimensional (1D) interpolating Hermitian finite elements 13 or Fourier series to approximate the mitral annulus from echo data. 36 An alternative method to reconstruct space curves that provides a variety of practical advantages is spline fitting.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on material models for mitral tissue are based on animal tissues and in-vitro tests (May-Newman and Yin 1995;Sacks et al 2002), but also some in-vivo studies have been published, mainly focusing of deformation patterns in different parts of the mitral complex (Sacks et al 2006;Eckert et al 2009;Göktepe et al 2009;Krishnamurthy et al 2008;Ryan et al 2008). Some initial in-vitro studies on human tissue constitutive modeling are provided by Prot et al (2010).…”
Section: Introductionmentioning
confidence: 98%